A recently extinct new species of Dryadobates (Anura: Aromobatidae) from South Brazil: species description and implications for the historical distribution and recent extinction history of the clade - Grant, Taran; Pinheiro, Paulo Durães Pereira (Zootaxa, 2025)
We describe a new species of Dryadobates on the basis of a single adult male collected in 1963 in Tarumã, Curitiba, Paraná, Brazil. Although the specimen is badly desiccated and extremely fragile, it can be readily assigned to Dendrobatoidea on the basis of its posterodorsally concealed tympanum, phalangeal swelling on finger IV, and tarsal keel. The new species shares with other species of Dryadobates the same morphology of finger discs II, IV, and V, absence of a metatarsal fold, presence of a complete pale oblique lateral stripe, absence of a pale dorsolateral stripe, presence of basal webbing between toes III–IV (absent between all other toes), presence of pale paracloacal marks, and small size. It is diagnosed from all nominal congeners by possessing a conspicuous pale oblique lateral stripe that is discrete and well defined along its entire length (i.e., not anteriorly indistinct). The type locality lies ca. 550 km south of the nearest congener in Angra dos Reis, Rio de Janeiro, suggesting the existence of additional Dryadobates populations between these localities. However, despite extensive surveys in suitable habitats at multiple localities in São Paulo and Paraná over the past 50 years, no other specimens of Dryadobates have been collected. Further, the region of the type locality—once characterized by forests, streams, and expansive fields and wetlands—has been transformed into a highly developed residential and commercial area lacking suitable habitat for Dryadobates, leading us to presume this species to be extinct. With the current species, Dryadobates now comprises seven described species, four of which disappeared within a 15–20-year window between the mid-1960s and mid-1980s. The drivers of these recent extinctions remain unclear, underscoring the urgent need to gather data on the natural history, distribution, and population status of extant Dryadobates species to inform effective conservation strategies.